Fanconi anemia and dyskeratosis congenita/telomere biology disorders: Two inherited bone marrow failure syndromes with genomic instability - Fiesco-Roa, Moisés Ó.; García-de Teresa, Benilde; Leal-Anaya, Paula; van ‘t Hek, Renée; Wegman-Ostrosky, Talia; Frías, Sara; Rodríguez, Alfredo (Frontiers in Oncology, 2022)
Inherited bone marrow failure syndromes (IBMFS) are a complex and heterogeneous group of genetic diseases. To date, at least 13 IBMFS have been characterized. Their pathophysiology is associated with germline pathogenic variants in genes that affect hematopoiesis. A couple of these diseases also have genomic instability, Fanconi anemia due to DNA damage repair deficiency and dyskeratosis congenita/ telomere biology disorders as a result of an alteration in telomere maintenance. Patients can have extramedullary manifestations, including cancer and functional or structural physical abnormalities. Furthermore, the phenotypic spectrum varies from cryptic features to patients with significantly evident manifestations. These diseases require a high index of suspicion and should be considered in any patient with abnormal hematopoiesis, even if extramedullary manifestations are not evident. This review describes the disrupted cellular processes that lead to the affected maintenance of the genome structure, contrasting the dysmorphological and oncological phenotypes of Fanconi anemia and dyskeratosis congenita/telomere biology disorders. Through a dysmorphological analysis, we describe the phenotypic features that allow to make the differential diagnosis and the early identification of patients, even before the onset of hematological or oncological manifestations. From the oncological perspective, we analyzed the spectrum and risks of cancers in patients and carriers.